The Association Between Hypertension and Non-Hemorrhagic Stroke - Desyanti Risky Putri; Saktivi Harkitasari; Sri Masyeni (Universitas Wijaya Kusuma Surabaya, 2026)
Background: Stroke is the leading cause of disability and the third leading cause of death worldwide. This study aims to investigate hypertension as a risk factor for non-hemorrhagic stroke (NHS). Methods: This study was designed as a retrospective, observational, analytic case-control study involving a total of 112 participants. Data analysis utilised the chi-square test, with a significance level set at p < 0.05 and a 95% confidence interval (CI). Results: The findings revealed that NHS patients were predominantly in the 45-60 year age group (44.6%), primarily male (69.6%), and mostly of Balinese ethnicity (94.6%). A significant number of NHS patients were diagnosed with hypertension (53.6%). The most frequently reported clinical symptoms were weakness or paralysis in the extremities (94.6%). An improvement in outcomes was observed in 80.4% of patients, with a median length of hospital stay of 4 days. Laboratory data were normal, and CT scans identified hypodense lesions in 60.7% of cases. The results of the chi-square statistical analysis indicated an odds ratio (OR) of 2.65, with a 95% CI of 1.22–5.74 and p = 0.013. In conclusion, this study suggests that hypertension increases the risk of non-hemorrhagic stroke by 2.65 times compared to individuals without hypertension.